New risk scoring system for predicting acute exacerbation of interstitial pneumonia after chemotherapy for lung cancer associated with interstitial pneumonia. (November 2018) - Isobe, Kazutoshi; Kaburaki, Kyohei; Kobayashi, Hiroshi; Sano, Go; Sakamoto, Susumu; Takai, Yujiro; Makino, Takashi; Tochigi, Naobumi; Iyoda, Akira; Homma, Sakae
Highlights: AE developed in 27.5% in lung cancer associated with IP during chemotherapy. The AE risk score was calculated with the formula. The AE incidence rate was 66.7% for a score of ≥11. The present AE score was able to identify high risk for AE after chemotherapy. Abstract: Background: Fatal acute exacerbation (AE) of interstitial pneumonia (IP) sometimes occurs after chemotherapy for lung cancer. We developed and evaluated a scoring system for assessing AE risk after chemotherapy in patients with lung cancer associated with IP. Methods: A review of medical records identified 109 patients with primary lung cancer associated with IP who had received chemotherapy at our center during the period from June 2007 through September 2017. We developed a model to score AE risk after chemotherapy in this patient group, and logistic regression was used to evaluate the model. Results: The anticancer agent score was determined by using AE rates reported in past studies. The risk score was calculated with the following formula: (1 × anticancer agent score) + (3 × smoking history [>70 pack-years]) + (4 × history of steroid use) + (3 × %diffusing capacity of lung carbon monoxide [<50%]). Patients were then classified into three groups. The AE incidence rate was 12% for a risk score of 0–5, 47% for a score of 6–10, and 66.7% for a score of ≥11. The sensitivity of the scoring system was 78.6% and specificity was 67.8%. Conclusions: The present scoring system was able to identify IP patients at high risk for AE after chemotherapy for lung cancer associated with IP.